BOOK REVIEW: ARIE SOVER, “JEWISH HUMOR. AN OUTCOME OF HISTORICAL EXPERIENCE, SURVIVAL AND WISDOM”, NEWCASTLE UPON TYNE: CAMBRIDGE SCHOLARS PUBLISHING, 2021, 323 P. - PRECUP, Amelia (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Jewish humor continues to spring interesting scholarly approaches. Only in the past decade this field of research has been enriched with the publication of valuable works by researchers such as Ruth R. Wise, Jeremy Dauber, or Louis Kaplan. Arie Sover’s latest book contributes to the field by revisiting the most commonly discussed aspects of Jewish humor, nuancing some popular claims regarding the roots of the Jewish humorous tradition, and updating the canon traditionally used for the exploration of the various manifestations of Jewish humor.